Persepsi Mahasiswa terhadap Penggunaan Media Pembelajaran Telegram, Canva dan Kahoot dalam Pembelajaran Prakarya dan Kewirausahaan - Mutmainah Mutmainah; Eriawaty Eriawaty; Sri Rohaetin (Edunomics Journal, 2026)
The rapid development of digital technology requires a transformation in entrepreneurship education to bridge the gap between theory and practical skills. This study aims to analyze student perceptions regarding the integration of Telegram, Canva, and Kahoot as learning media in the Craft and Entrepreneurship (PKWU) course. This research employed a descriptive quantitative approach involving 30 students selected through purposive sampling. Data were collected via a 5-point Likert scale questionnaire covering indicators of ease of use, feature completeness, material comprehension, visual appeal, and learning motivation. The results indicated a highly positive perception among students, with an average agreement rate of 87.3%. Specifically, Telegram was perceived as an efficient management system for material distribution, Canva as a vital tool for developing creative product branding, and Kahoot as an effective gamification tool to enhance engagement and evaluation. The findings suggest that the synergy of these three platforms creates a comprehensive digital learning ecosystem that simulates professional workflows. This study implies that the strategic integration of diverse digital media can significantly foster entrepreneurial mindsets and technical competencies in higher education.